A physics‐based threshold voltage model of AlGaN/GaN nanowire channel high electron mobility transistor. Issue 1 (22nd September 2016) - He, Yunlong; Zhai, Shaopeng; Mi, Minhan; Zhou, Xiaowei; Zheng, Xuefeng; Zhang, Meng; Zhang, Peng; Yang, Ling; Wang, Chong; Ma, Xiaohua; Hao, Yue
Abstract : A new simple model of threshold voltage for AlGaN/GaN nanowire channel high electron mobility transistors (NC‐HEMTs) is built in this work. Firstly, four NC‐HEMTs with different nanowire channel width are fabricated, and the conventional HEMT is produced for comparison. With the nanowire channel width decreasing, the threshold voltage of NC‐HEMTs moves positively. Then, the dependence of electron concentration on the nanowire channel width is studied by Silvaco simulation software. With the nanowire channel width decreasing, the electron concentration reduces. Finally, we recognize the threshold voltage model of conventional HEMT for NC‐HEMT modeling, and the new model of threshold voltage of NC‐HEMT is obtained. This model can explain the dependence of electron concentration on nanowire channel width. The depletion region width formed by side gate is about 37 nm which is obtained by the equation of the new model.